2023
DOI: 10.3847/2041-8213/acae25
|View full text |Cite
|
Sign up to set email alerts
|

Overmassive Black Holes in Dwarf Galaxies Out to z ∼ 0.9 in the VIPERS Survey

Abstract: Supermassive black holes (SMBHs) are thought to originate from early universe seed black holes of mass M BH ∼ 102–105 M ⊙ and grown through cosmic time. Such seeds could be powering the active galactic nuclei (AGN) found in today’s dwarf galaxies. However, probing a connection between the early seeds and local SMBHs has not yet been observationally possible. Massive black holes hosted in dwarf galaxies at intermediate redshifts, on the other hand, may repr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 94 publications
2
22
0
Order By: Relevance
“…Interestingly, Bogdan et al (2023) reported the discovery of a gravitationally lensed quasar at z = 10.3, with an estimated black hole mass comparable to its stellar mass, and Natarajan et al (2023) suggested its origin as a heavy black hole seed. However, the detection of overmassive black holes is not new, as it was already suggested by sporadic observations at z ∼ 6 in the pre-JWST era (see, e.g., Wang et al 2010), and, recently, even more locally (see, e.g., Mezcua et al 2023, up to z = 0.9).…”
Section: Local Scaling Relationmentioning
confidence: 82%
“…Interestingly, Bogdan et al (2023) reported the discovery of a gravitationally lensed quasar at z = 10.3, with an estimated black hole mass comparable to its stellar mass, and Natarajan et al (2023) suggested its origin as a heavy black hole seed. However, the detection of overmassive black holes is not new, as it was already suggested by sporadic observations at z ∼ 6 in the pre-JWST era (see, e.g., Wang et al 2010), and, recently, even more locally (see, e.g., Mezcua et al 2023, up to z = 0.9).…”
Section: Local Scaling Relationmentioning
confidence: 82%
“…An example of a similar bias can be seen in Figure 18 of Burke et al (2022), where their M BH values of variability-selected active dwarf galaxies are 2-3 dex above the M BH −M å scaling relation. Similarly, Mezcua et al (2023) also found a sample of distant active dwarf galaxies containing overmassive MBHs. It is The error of M BH is 0.55 dex, i.e., the scatter of the scaling relation in Reines & Volonteri (2015), compared to which the M å uncertainty is negligible.…”
Section: Challenges That May Lead To the λ Edd Tensionmentioning
confidence: 78%
“…Indeed, the luminosity threshold of 10 41 erg s −1 imposes a lower black hole mass limit (per Eddington ratio), so HLXs may represent the massive end of the IMBH distribution. We note that the predicted lower black hole mass limits will be larger if the evolution of the overall sample is dominated by a mass scaling relation with a shallower slope at low black hole masses (e.g., Mezcua 2017;Pacucci et al 2018) or if some of the black holes evolved to be over massive when compared to the scaling relations (e.g., Mezcua et al 2023;Pacucci et al 2023).…”
Section: Constraints On the Black Hole Mass Distribution Of Hlxsmentioning
confidence: 88%